Factors influencing parents in selecting school for children with special education needs - Abdullah, Muhammad Faris; Ahmad Shuhaimi, Ainul Ashiqin; Mohamed Osman, Mariana; Rabe, Noor Suzilawati (2017)
Equal access to education is an essential element in achieving community well-being, hence it is crucial that the educational facilities provided to be equally accessible for children with special education needs. In Malaysia, one of the special education programme provided in mainstream public schools is known as the Program Pendidikan Khas Integrasi (PPKI), which is an effort towards inclusive education. The objective of this study includes: (i) to analyse the factors influencing the decision of parents in selecting school for their special children, and (ii) to assess the issues and problems faced by parents in selecting schools for their children with special needs. The study determines parents’ criteria in selecting school for their children with SEN among 134 parents of children in PPKI via questionnaire survey. Semi-structured interview was conducted among 12 teachers of PPKI, the findings were used to validate the survey finding. Findings from these two methods were consolidated, result shows that school selection for children with special needs are greatly associated with the school facility. Hopefully, the paper will benefit the local authority in planning for educational facility, as well as benefit special needs children in regards to the educational facility for special education provision in a community.